2022
DOI: 10.1002/agg2.20234
|View full text |Cite
|
Sign up to set email alerts
|

Response of chickpea to varying moisture stress conditions in Ethiopia

Abstract: Chickpea (Cicer arietinum L.) is an economically important crop grown by nearly one million Ethiopian smallholder farmers. The crop is often considered as “stress‐loving,” but moisture stress at flowering and grain filling stages could be detrimental. Yield of chickpea is commonly affected by terminal drought stress in the rainfed production system in Ethiopia. The lack of proper field‐screening methods has hindered the development of drought‐tolerant varieties. This study demonstrates a simple and practical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…S2 ). These results are in accordance with previous studies on chickpea ( Zaman-Allah et al , 2011 ; Vadez et al , 2012 ; Korbu et al , 2022 ), which suggest that water availability during the pod-filling period is crucial for improving seed yield under water deficit. Our results revealed that the first mega-environment experienced mild drought stress during the pod-filling stage ( Supplementary Table S4 ); hence, seed yield was found to be positively correlated with days to maturity in this mega-environment.…”
Section: Discussionsupporting
confidence: 93%
“…S2 ). These results are in accordance with previous studies on chickpea ( Zaman-Allah et al , 2011 ; Vadez et al , 2012 ; Korbu et al , 2022 ), which suggest that water availability during the pod-filling period is crucial for improving seed yield under water deficit. Our results revealed that the first mega-environment experienced mild drought stress during the pod-filling stage ( Supplementary Table S4 ); hence, seed yield was found to be positively correlated with days to maturity in this mega-environment.…”
Section: Discussionsupporting
confidence: 93%
“…From this, the importance of pulse crops such as chickpea cannot be overlooked because of its major role in balancing the ecosystem, generating income, sustaining food security, and in increasing the foreign exchange of the country. Chickpea is an economically important crop grown by around one million Ethiopian smallholder farmers (Korbu et al 2022). The Ethiopian chickpea production shares 90% of the total production in sub-Saharan Africa and 3% of the world's production, and this makes Ethiopia the sixth among the world's major chickpea producers (Getahun et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chickpea is an economically important crop grown by around one million Ethiopian smallholder farmers (Korbu et al. 2022). The Ethiopian chickpea production shares 90% of the total production in sub‐Saharan Africa and 3% of the world's production, and this makes Ethiopia the sixth among the world's major chickpea producers (Getahun et al.…”
Section: Introductionmentioning
confidence: 99%
“…They are an excellent choice for vegetarians as they are low in fat, high in fi ber and complex carbohydrates, and a good source of vitamins and minerals [5][6][7]. Ethiopia is the leading producer, consumer, and exporter of chickpeas in Africa, mainly grown by smallholder farmers in rain-fed areas [8][9][10][11][12][13][14]. According to the Central Statistical Agency [15], nearly 57% of total chickpea production in Ethiopia is consumed by households, with the remainder exported.…”
Section: Introductionmentioning
confidence: 99%